Building Critical Thinking Skills Through a New Design Mobile-Based Interactive Learning Media Knowledge Framework - Ninghardjanti, Patni; Dirgatama, Chairul Huda Atma (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Education is expected to be a solution to issues in human resource development. A number of initiatives have been made to overcome educational problems ranging from improving the curriculum, developing and increasing the quality of teachers, developing student abilities, and other efforts related to improving the quality of education. Based on the preliminary observation, students’ critical thinking skills were considered low and a confirmatory study related to building critical thinking skills is necessary. This study analyzed critical thinking skills that are built based on perceptions of mobile media, self-directed learning, and digital literacy. The research method used was a quantitative approach by using a questionnaire instrument.. Data analysis included analyses of prerequisite tests including validity and reliability tests. The data were analyzed using the structural equation model (SEM) analysis. The results showed that 1) there was a positive and significant effect on the variable of perceptions on online learning media on self-directed learning and digital literacy, 2) there was a positive and significant effect on the variable of self-directed learning on critical thinking skills 3) there was a positive and significant effect on the variable of digital literacy on critical thinking skills 4) the variable of the perceptions on mobile-based learning media had a positive and significant effect on critical thinking skills through the mediation of self-directed learning and digital literacy.